Introduction to Biology. - Wilson, David L. (11th Hour., 2009)
Visit www.blackwellpublishing.com/11thhour for additional information. This book reviews the more challenging material in a college-level, introductory course in biology. It is intended to supplement standard textbooks in biology, or for students who wish to review such material. '11th Hour: Introduction to Biology' is of particular use to students enrolled in a majors or non-majors introductory biology course, or students taking AP biology. It concentrates on those topics that usually give students the most difficulty, and problems/questions are rated throughout in terms of their level of dif.